Analyzing the content of digital skills books for the first intermediate grade in the Kingdom of Saudi Arabia in light of the principles and foundations of the constructivist theory - Al-Qahtani, Maha Missmar; Al-Shibl, Manal AbdulRahman (Journal of Curriculum and Teaching Methodology, 2022)
This research aimed at a multi-skilled digital educational content for the first intermediate grade in the principles and foundations of the far theory, in terms of prior knowledge, self-knowledge building, change in infrastructure, facing the situation, legal policy for the first social grade, and the research followed the descriptive-analytical approach (analysis (Content), and the sample of the analysis consisted of three units of digital skills, the first semester and the second semester of the first grade. Self-knowledge (5) indicators, the change in the knowledge infrastructure (4) indicators, indicators, indicators, background indicators (4) performance indicators with varying percentages and frequencies, where the total frequency of the indicators of the research tool axes reached (1701) times, and it ranked first The axis of building self-knowledge, with a frequency of (596) skills, and a total percentage of (35%) repeat (337) m and a percentage, and percentage, 20% among the axes, and a third neighboring (16%) among the axes, and in the first place recommended by the researcher. Various educational boxes.
Keywords: content analysis; constructivist theory; principles of constructivist theory; digital skills course